Experimental study on precast concrete moment‐resisting frame system with sector lead viscoelastic dampers. Issue 7 (14th April 2021) - Wu, Congxiao; Li, Dingbin; Deng, Xuesong; Yang, Cheng; Xu, Xin
Summary: Connection failure between precast components greatly increases the risk of collapse of a precast concrete (PC) frame during earthquakes. In this study, a PC frame structure system with sector lead‐viscoelastic damper (SLVD) is proposed, in which the SLVD not only protects the wet connection but also absorbs input energy in earthquakes. Two two‐storey two‐bay PC frame were constructed, one without SLVD (PC specimen) and the other with SLVDs (PS specimen). These PC frames were tested under cyclic loading and compared to an analogous monolithic frame (RC specimen). The differences in hysteretic curves, bearing capacity, strength and stiffness degradation, and energy dissipation capacity of the three specimens are compared in detail to investigate the impact of SLVD on the seismic performance of the PC frame. The experimental results show that the bearing capacity of the PS specimen in positive and negative loading directions increased by 42.53% and 31.26%, respectively, compared with the PC specimen. The ultimate deformation capacity and ductility of the PS specimen were better than those of the PC specimen. The seismic performance of the precast frame with SLVDs was similar to that of the monolithic reinforcement frame structure.